2004
DOI: 10.2514/1.144
|View full text |Cite
|
Sign up to set email alerts
|

Development of Powered Resonance-Tube Actuators for Aircraft Flow Control Applications

Abstract: The present paper addresses both active-flow-control actuator technology development and the demonstration of the effectiveness of actuators that could be easily integrated into practical aircraft applications. The actuator used is an adaptation of the Hartmann oscillator. Demonstration experiments that illustrate the effectiveness of this actuator include cavity tone suppression at transonic speeds and the reduction of jet-impingement tones. The actuator concept is based on a high-speed jet aimed at the mouth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, for the droplets with different initial diameters, the resonance frequency happens at different values and modes, which means that for a specific acoustic frequency, when the resonance frequency of the droplet matches the acoustic frequency, the shape oscillation will reach its maximum. On the other hand, the SPL of the acoustics only affects the specific deformation amplitude, as described in Equations (8) and (21). As with the discussion for cases with different cavity lengths and nozzle pressure ratios in Figure 14.…”
Section: Effect Of Initial Droplet Diametermentioning
confidence: 83%
See 1 more Smart Citation
“…However, for the droplets with different initial diameters, the resonance frequency happens at different values and modes, which means that for a specific acoustic frequency, when the resonance frequency of the droplet matches the acoustic frequency, the shape oscillation will reach its maximum. On the other hand, the SPL of the acoustics only affects the specific deformation amplitude, as described in Equations (8) and (21). As with the discussion for cases with different cavity lengths and nozzle pressure ratios in Figure 14.…”
Section: Effect Of Initial Droplet Diametermentioning
confidence: 83%
“…Michael et al [20] compared the flow characteristics of a HRT, with and without shielding, with the SA one-equation turbulence model, and they reported that the presence of a shield caused intense flow/shock oscillation around the cavity mouth. Raman et al [21] concluded that properly designed HRT had significant advantages over conventional actuators, such as acoustic, piezo, and oscillatory microstructures, and could be widely used in an active-flow-control field.…”
Section: Introductionmentioning
confidence: 99%
“…Hartmann acoustic generator mainly consists of nozzle and circular resonant cavity which is characterized by simple construction, low cost and producing high intensity sound in liquid [6,7]. The Hartmann acoustic generator is one such device which can be effectively used in numerous applications such as coagulating and precipitating dust and smoke using sound waves, atomization, active noise control and ignition device of rocket engine in aviation field [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is surprising that the potential of this incredibly simple device has not been fully exploited. Murugappan and Gutmark [17], Kastner et al [18], Raman and Kibens [19], and Raman et al [20] have investigated the application of PRTs for controlling high speed flows. The use of the PRT and other active flow control actuators is also described in a review paper by Raman and Cain [21].…”
mentioning
confidence: 98%